KOMUNIKASI DESTINATION BRANDING LEREH LEREH BWI 1 TV DALAM MEMBENTUK IDENTITAS DAERAH - Moch. Nuril Anwar; Mariyatul Qiptiyah; Siti Holiza Fitriana; Fasya Rina Sitajeng; Inayatul Maghfiroh (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
This research aims to analyze the strategy of the "Lereh Lereh" program on the local television station BWI 1 TV in constructing tourism and culinary identities in Banyuwangi Regency. Amidst digital media disruption, local television faces significant challenges in remaining relevant as a cultural agent. Using a descriptive qualitative method with a case study approach, data were collected through in-depth interviews, observation, and content analysis. The results indicate that BWI 1 TV implements three main strategic pillars: history-based narrative selection (framing), visualization of local cultural symbols, and digital platform synchronization. The program has successfully transformed audience perceptions of culinary and tourism from mere commodities into ancestral heritage that must be preserved. Theoretically, the program fulfills the cycle of social construction through the stages of objectification, internalization, and externalization, triggering the emergence of collective pride (social validation). This study concludes that technological adaptation and consistency in local narratives are key for regional television media to maintain their existence while strengthening regional identity in the era of globalization.